A Golden Access to Acenopentalenes. Issue 11 (5th February 2018) - Wurm, Thomas; Rüdiger, Elias C.; Schulmeister, Jürgen; Koser, Silke; Rudolph, Matthias; Rominger, Frank; Bunz, Uwe H. F.; Hashmi, A. Stephen K.
Abstract: By employing gold catalysis, starting from dialkynylated acenes a series of novel un‐symmetrical aceno‐annulated dibenzopentalenes has been prepared. The achieved yields range from 62–68 %. The fused systems contain naphthalene, anthracene, tetracene, and pentacene units. All new compounds are soluble and stable under standard conditions. The optical properties of the systems are dominated by the dibenzopentalene core for the smaller representatives, while for the anthracene‐pentacene‐based aceno‐benzopentalenes the optical properties of the acene group dominates. Preliminary morphology tests on thin films showed a reverse trend between crystal size and molecule size. Abstract : Simply gold : A simple access to acenopentalenes was opened by gold catalysis. The optical properties are dominated by the benzopentalene core for the smaller derivatives while the acene core takes the lead for π‐extended systems.